Association of periconceptional or pregnancy exposure of HPV vaccination and adverse pregnancy outcomes: a systematic review and meta-analysis with trial sequential analysis - Yan, Xiaoli; Li, Hongyu; Song, Bin; Huang, Ge; Chang, Qing; Wang, Dan; Yan, Ping (Frontiers in Pharmacology, 2023)
Abstract Objective: To evaluate whether periconceptional or pregnancy exposure of human papillomavirus (HPV) vaccination would increase the risk of adverse pregnancy outcomes. Methods: The PubMed, Web of Science, Embase, the Cochrane Library of clinical trials were searched from inception to March 2023. We computed relative risk (RR) and 95% confidence intervals (CIs) and prediction intervals (PIs) regarding the association between HPV vaccination in periconceptional period or during pregnancy and the risks of adverse pregnancy outcomes by using R software Version 4.1.2 and STATA Version 12.0. A trial sequential analysis (TSA) was performed with TSA v0.9.5.10 Beta software. Results: Four randomized controlled trials (RCTs) and eight cohort studies were included in this meta-analysis. Analysis of RCTs showed that HPV vaccination in periconceptional period or during pregnancy did not increase the risks of spontaneous abortion (RR=1.152, 95% CI: 0.909-1.460, 95% PI: 0.442-3.000), birth defects (RR=1.171, 95% CI: 0.802-1.709, 95% PI: 0.320-4.342), stillbirth (RR=1.053, 95% CI: 0.616-1.800, 95% PI: 0.318-3.540), preterm birth (RR=0.940, 95% CI: 0.670-1.318) and ectopic pregnancy (RR=0.807, 95% CI: 0.353-1.842, 95% PI: 0.128-5.335). In cohort studies, periconceptional or pregnancy exposures of HPV vaccine were not associated with the increased risk of spontaneous abortion (RR=0.987, 95% CI: 0.854-1.140, 95% PI: 0.652-1.493), birth defects (RR=0.960, 95% CI: 0.697-1.322, 95% PI: 0.371-2.480), stillbirth (RR=1.033, 95% CI: 0.651-1.639, 95% PI: 0.052-21.064), small size for gestational age (SGA) (RR=0.971, 95% CI: 0.873-1.081, 95% PI: 0.657-1.462) and preterm birth (RR=0.977, 95% CI: 0.874-1.092, 95% PI: 0.651-1.444). Conclusion: HPV vaccine exposures in periconceptional period or during pregnancy did not increase the risks of adverse pregnancy outcomes, including spontaneous abortion, birth defects, stillbirth, SGA, preterm birth and ectopic pregnancy.